Antimicrobial activity of Lactobacillus fermentum TcUESC01 against Streptococcus mutans UA159. (May 2020) - Rodrigues, Jeisa Zielle de Souza; Passos, Manuela Ribeiro; Silva de Macêdo Neres, Nayara; Almeida, Rafael Silva; Pita, Louise Soares; Santos, Iago Almeida; Santana Silveira, Paulo Henrique; Reis, Mariane Mares; Santos, Isabella Porto; de Oliveira Negrão Ricardo, Luccas; Lima, Brenda Oliveira; D'Orleans Farias Marinho, Patrick; et al.
Abstract: Dental caries is a multifactorial chronic-infection disease, which starts with a bacterial biofilm formation caused mainly by Streptococcus mutans . The use of probiotics has shown numerous health benefits, including in the fight against oral diseases. Strains of Lactobacillus fermentum have already shown probiotic potential against S. mutans, but there are still few studies. Thus, the aim of our study was to evaluate the antimicrobial activity of the inoculum and metabolites produced by L. fermentum TcUESC01 against S. mutans UA159. For this, a growth curve of L. fermentum was performed and both the inoculum and the metabolites formed in the fermentation were tested against the growth of S. mutans UA159 in agar diffusion tests, and only its metabolites were tested to determine the minimum inhibitory concentration, minimal bactericidal concentration and inhibition of cell adhesion. Inhibition of biofilm formation, pH drop and proton permeability were also tested with the metabolites. The zone of inhibition began to be formed at 14 h and continued until 16 h. The inoculum containing L. fermentum also showed zone of inhibition. The MIC for the metabolites was 1280 mg/mL and the MBC was obtained with a concentration higher than the MIC equal to 5120 mg/mL. Half of the MIC concentration (640 mg/mL) was required to inhibit S. mutans adhesion to the surface of the microplates. In the biofilm analyzes, the treatment with the metabolites in the tested concentration was not able to reduce biomass, insoluble glucans and alkali soluble compared to the control biofilm ( p > 0.05). The metabolites also did not affect acid production and acid tolerance of S. mutans cells in biofilms compared to saline group ( p > 0.05). Lactic acid (50.38%) was the most abundant organic acid produced by L. fermentum . This is the first report showing that the metabolites produced by the Lactobacillus fermentum TcUESC01 have a potential to be used as an antimicrobial agent against S. mutans, showing anti-adherence and bactericidal activity against planktonic cells of S. mutans . Thus, further studies should be carried out in order to better understand the antimicrobial activity of metabolites of L. fermentum TCUESC01. Highlights: First report of antimicrobial activity of L. fermentum TcUESC01. These metabolites had potential anti-adherence and bactericidal effect against planktonic cells of S. mutans UA159. Identification of metabolites produced by L. fermentum TcUESC01.